Fondi In Focus: Boost Student’s Vocabulary Mastery in Senior High School - Rahma Pebriyanti; M. Sofian Hadi (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study investigates the effectiveness of the Fondi application in enhancing students’ English vocabulary acquisition at the senior high school level. A quantitative method with a pre-experimental one-group pre-test and post-test design was employed. The research was conducted at SMA Negeri 1 Rumpin, Bogor, involving 27 tenth-grade students selected through cluster sampling. Data were collected through pre-test and post-test instruments and analysed using the Wilcoxon Signed-Rank Test. The findings revealed that the mean pre-test score was 44.48, while the mean post-test score increased to 71.25. The statistical analysis yielded a Z value of -4.542 with a significance level of 0.000 (<0.05), indicating a significant difference between the pre-test and post-test results. Consequently, the alternative hypothesis (H1) was accepted, confirming that the Fondi application effectively enhances students’ vocabulary mastery.